Silver nanoparticles/silver chloride (Ag/AgCl) synthesized from Fusarium oxysporum acting against Klebsiella pneumouniae carbapenemase (KPC) and extended spectrum beta-lactamase (ESBL). Issue 2 (March 2016) - Picoli, Simone U; Durán, Marcela; Campinas, Campinas; Andrade, Patricia F; Duran, Nelson
No abstract available